PREDICTORS OF PHYSICAL ACTIVITIES PRACTICE IN CHILDREN AND ADOLESCENTS - Castillo, Isabel; Balaguer, Isabel; Tomás, Inés (Anales de Psicología / Annals of Psychology)
The aim of the present work is to analyze the influence of some personal, social and ambiental factors in the exercise and sport practice, in a sample of 283 students (146 boys and 137 girls) between 11 and 17 years old, using the Health Behavior School-Children Questionnaire (Wold, 1989). The results show that personal and ambiental factors analyzed are positive related to sport and exercise practice in both boys and girls groups. In relation with social factors, only the facility for doing friends at school is related to exercise practice in boys group; in girls group the social factor that is positive related to exercise and sport practice is the old brother sport practice.